Fracaso universitario: ¿ilusión o realidad? - Pompa, Ángel Luis; Ponz, Noemí; Rama, Vanessa; Ríos, José Antonio (REOP - Revista Española de Orientación y Psicopedagogía, 2014)
RESUMEN Son numerosos los estudios que hacen referencia al fracaso escolar, pero pocos los que se centran en la etapa universitaria. Diversos factores condicionan la elección de carrera, la valoración del profesorado, la atribución (externa o interna) de los resultados o las consecuencias del suspenso. Cada uno de ellos se manifiesta en mayor o menor grado en diferentes carreras universitarias. ABSTRACT They are enormous the studies which make reference to the school failure but few of them are adjusted to the university aged. Several key factors put into working order the choice of the career, the evaluation of the teaching staff, the attribution (external or internal) of the results of the consequences of the fail. Each of them are revealed with more or less importance in different university careers.